Global Attractivity and Periodic Character of Difference Equation of Order Four. (31st October 2012) - Obaid, M. A.; Elsayed, E. M.; El-Dessoky, M. M.
Abstract : We investigate the global convergence result, boundedness, and periodicity of solutions of the recursive sequence x n + 1 = a x n + ( ( b x n - 1 + c x n - 2 + d x n - 3 ) / ( α x n - 1 + β x n - 2 + γ x n - 3 ) ), n = 0, 1, …, where the parameters a, b, c, d, α, β, and γ are positive real numbers and the initial conditions x - 3, x - 2, x - 1, and x 0 are positive real numbers.